(untitled) (Nigerian Journal of Technology, 2015)
In this paper, the base study for improving the transient stability of Nigerian 330kV transmission network using Static Var Compensation (SVC) is conducted with the focus of developing indices that can appropriately size and locate SVC within the network. The study is performed using commercially available software Dig SILENT Power Factory. The overloaded lines which could excite instability in the network are identified. Fixed capacitor thyristor controlled reactor is used to model the SVC and is appropriately sized and located within the network. Transient stability of the network is analysed by determining the critical clearing time of the acute generators when a balanced three phase fault is applied to the middle of the critical lines within the network using step-by step technique. Some of the key results reveal that the lines: Jebba- Osogbo, Shiroro-Kaduna, Benin-Sapele and Benin-Onitsha are the critical lines within the network. The Critical Clearing Times (CCTs) of the acute generators when 3-phase fault is applied at Jebba- Osogbo and Shiroro-Kaduna transmission lines are 380ms and 480ms, respectively. However, generators located at Afam and Sapele that are close to Benin-Sapele and Benin-Onitsha transmission line, respectively are always losing synchronism to 3-phasefault of any duration. Appropriately sized SVCs with values 124Mvar, 73Mvar, 62Mvar and 110Mvar located at Osogbo, Kaduna and Benin compensated the network and increase the CCTs to 470ms, 500ms, 220ms and 120ms, respectively. http://dx.doi.org/10.4314/njt.v35i1.23